Pendampingan Digital Marketing dan Diferensiasi Produk bagi UMKM Kopine Inyong di Desa Melung - Agung Prasetyo; Ilham Albana; R. Satria Setyanugraha; Hanif Fadhil Abdullah; Sugeng Pambudi (PADMA, 2025)
The Kopine Inyong MSME in Melung Village struggles with limited product innovation, simple marketing, and manual business management. This community service aims to improve competitiveness through packaging innovation, digital marketing, and business digitization. Activities include training, packaging design, and digital record-keeping. The program resulted in new sachet and Ready-to-Drink (RTD) products, better digital promotion skills, and more efficient management. It strengthened MSME independence and supported the local economy.